Foundation Fieldbus Interoperability Testing (Honeywell) - Najla Fatie Binti Mohamad Sukry, Najla Fatie (2010)
This project is to perform the technical verification and interoperability of Foundation Fieldbus host and devices. Fieldbus technology has come out with many advantages over the existing distributed control systems.